PERAN IBU PEKERJA DALAM MENDIDIK ANAK: ROLE OF MOTHER WORKERS IN EDUCING CHILDREN (NOURA: Jurnal Kajian Gender dan Anak, 2018)
Times of millenial, no wonder many mothers to be a worker, from workers laborers to office workers. It is not just to the demands of life but also has become a lifestyle of the youn mother, especiallly to self-actualize after pursuing higher education. The role of mother is divided two, first as a mother of children at home an the second bering a worker, both of which are required to be a professional in their field.Mother as a workers, still should be able to be the primary educator for her children. Ranging from educating the basic things such as a build positive character for children, be an example, gave a true in attitude an behavior as well as teach a smart kids in a sociable and able to develop age-appropriate development.Therefore, mother should be able to divide the time, when at home in serving her husband an children or in the work to become a skilled worker and reliable. Working mother is a mother who is tough and can still be balanced in educating children as well as pursue a good career.